Association between serum platelet level and dermatitis rash: Results from the China Health and Nutrition Survey - Yue Jiang; Ding Li; Xiaojie Ding; Zhan Zhang; Xiaoxuan Ma; Haotian Xu; Guangyuan Cheng; Ying Zhang; Yi Ru; Ying Luo; Wencheng Jiang; Ruiping Wang; et al. (PLoS ONE, 2026)
Dermatitis rash (DR), a prevalent inflammatory skin disorder marked by erythema, pruritus, and scaling, poses diagnostic challenges due to overlapping phenotypes with atopic dermatitis and psoriasis. This study examines the relationship between serum platelet (PLT) levels and DR, as the PLT-DR link remains unknown. We used the China Health and Nutrition Survey (CHNS) database, 7,337 participants (172 DR cases, 7,165 controls) were analyzed. Baseline characteristics were compared via weighted chi-square tests. Multifactor regression models and weighted logistic regression assessed the PLT-DR relationship, while restricted cubic splines (RCS) explored nonlinear associations. The impact of age and sex was also evaluated. We found PLT levels significantly reduced DR risk (model 1: odds ratios ( OR ) = 0.9974 [95% confidence intervals (CI) = 0.9951–0.9998], P = 0.0316; model 2: OR = 0.9976 [95% CI = 0.9953–0.9999], P = 0.0490; model 3: OR = 0.9975 [95% CI = 0.9950–0.9999], P = 0.0398). Covariates such as previous smoking and rural residency were significantly associated with DR. Nonlinear models and risk stratification confirmed these findings, with female sex moderating the PLT-DR relationship. This elucidates that higher PLT levels may independently lower DR risk, suggesting diagnostic potential. PLT thresholds may enhance risk prediction models, aiding early intervention in high-risk populations.